A singular Trudinger–Moser inequality on compact Riemann surface with smooth boundary. Issue 3 (4th March 2023) - Yu, Pengxiu
Abstract : Let ( M, g ) be a compact Riemann surface with smooth boundary. In this paper, using blow-up analysis, we prove the existence of an extremal function for a singular Trudinger–Moser inequality on ( M, g ) .